Lim Ju Gyeong’s Social Masks in True Beauty - Stephanie Devina; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2022)
The use of social masks can help a person to meet certain societal standards. In True Beauty, the main character, Lim Ju Gyeog uses cosmetics and fashion as her social masks to fulfill Korean beauty and fashion standards. By achieving the standards, Ju Gyeong is being socially accepted and admired. Ju Gyeong’s social masks take the roles as her self-protection against her fear and to boost her self-esteem to value her worth.Ju Gyeong is considered to be beautiful and fashionable because she is able to meet the societal standards of beauty and fashion. The meaning of beauty and fashionable are fluids that can be different from one place to the other. The use of social masks brings impact to a wearer’s life.